Hubungan modifikasi kadar natrium dialisat dengan phase angle pada pasien hemodialisis reguler - Nurfatimah Itoni Ritonga; Syafrizal Nasution; Abdurrahim Rasyid Lubis (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Introductions : Uncontrolled blood pressure and persistant overload extracelluler fluid caused by the positif balance of sodium and water, is the contributor of left venticular hipertrophy in hemodialytic patients and will influeate to cell integrity. Sodium dialysate level modification is one of the method to solve this matter. Phase angle is the method to examine the cell integrity in hemodialysis patients. The aim of this study was to determinethe correlation betweenmodifications of sodiumdialysatewith phase angle in regularhemodialysispatientsMethods : An experimental studydesignfromMay untilDecember 2014in28regularhemodialysis patients. By comparing phase angle at pre hemodialysis before and after sodium dialysate modificationResults : Of the 28 subjects, we found 16 male patients (57.1%) and female 12 patients (42.9%) with mean phase angle after sodium dialysate modification higher compare than before modification (5.83 vs 5.80). But there is no significant difference in statistic (p=0.145)Conclusion : There is no significant difference in phase angle between before and after sodium dialysate modification. Keywords : Hemodialysis, modificationof sodiumdialysate, phase angle.